An outlook on modern and sustainable approaches to the management of grape pomace by integrating green processes, biotechnologies and advanced biomedical approaches. (November 2022) - Perra, Matteo; Bacchetta, Gianluigi; Muntoni, Aldo; De Gioannis, Giorgia; Castangia, Ines; Rajha, Hiba N.; Manca, Maria Letizia; Manconi, Maria
Graphical abstract: Highlights: The great potential of grape pomace valorisation lies in phytochemicals extraction. Phytochemicals extraction achieves a lower environmental impact. A transition of the wine-chain towards circular economy is possible. Residue valorisation can increase the competitiveness of agro-industrial sector. Abstract: Grape pomace is the main solid residue of wine industry, mainly composed of seeds, skins and stalks, all containing high amounts of valuable phytochemicals. Considering its high potential, in this review, an outlook on different resources and products, which can be obtained by the recovery of grape pomace is provided. Special attention has been devoted to the analysis of chemical, physical and biotechnological processes to be applied and also to the high value compounds and products, such as supplements, nutraceuticals and cosmeceuticals, that can be manufactured. In particular, in the first part of the review, an update on the composition of grape pomace has been provided along with the analysis of its traditional fate. In the second part, the more modern and green approaches tested to the sustainable management of grape pomace are reported and discussed.